Hubungan Kadar Hb Ibu Inpartu Terhadap Kejadian BBLR di RSUD Kabupeten Nganjuk Periode Bulan Maret-April Tahun 2013 - Eny Sendra; Clairine Maretha Martin Putra (coba, 2015)
The report of the Health Office District/City Health on 2012, It is known that the number of LBW baby in East Java is 3,32% .And the number of LBW birth in Kediri is 2,24% . There are lower than the rate of LBW births in Nganjuk. The LBW births in Nganjuk is 3.39%. There found 260 cases in 2012 and 272 cases in 2013. LBW is one of the biggest causes of neonatal death. LBW can be caused by many factors, There are maternal factors, fetal factors, placental factors and eviromental. The purpose of this study is for knowing relation hemoglobin rate inpartu mother against the incidence of low birth weight. The population of this study used 31 respondent who mother give birth to LBW baby by simple Random sampling techniques, It get 29 sample of mother who give birth to LBW baby. These variables of study are measured by documentation guideline, the results of the status medical record patients. This study method use Cross Sectional design by independent variable of hemoglobin rate inpartu mother and dependent variable of the incidence of LBW by using the Spearman Rank Test. The result from Spearman Rank analysis there was not relation Hb rate inpartu mother against incidence of low birth weight ( calculate ρ = - 0,031 and ρ table 5% = 1,699 so calculate ρ < ρ table) so it can be concluded that Ho is accepted at significance level 0.05. It can conclude so there is no relation Hb rate inpartu mother against incident of low birth weight. Keywords: low birth weight, maternal Hb inpartu